Factors that make the language program of the center for continuous education of Escuela Politécnica Nacional successful from the perspective of instructors, students and leaders of the institution - Salazar Chicaiza, Mónica Yadira (2020)
To determine the factors that make the language program of The Center for Continuous Education of Escuela Politécnica Nacional (CEC-EPN) successful.